The differential equations of some differential geometrical objects - Bliznikas, V. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. И. Близникас. Дифференциальные уравнения некоторых полей дифференциально-геометрических объектовV. Bliznikas. Kai kurių diferencialinių geometrinių objektų diferencialinės lygtys